The Influence of Work Professionalism and Communication on Loyalty Safety Operational Employees Railroad Crossings (Study At The Garut Regency Transportation Agency) - Cepi Supriadi; S Ridwan; Deden Komar Priatna (Greenation International Journal of Law and Social Sciences, 2023)
This study aims to investigate the influence of work professionalism and communication on the loyalty of employees working in railway crossing safety operations at the Garut Regency Transportation Service. The study examines variables such as competence, professionalism, communication, and employee loyalty, with professionalism and communication as independent variables and loyalty as the dependent variable. Sedarmayanti's (2017) theory of professionalism, which includes competence, effectiveness, efficiency, and accountability, and Effendy's (2015) communication theory, encompassing attitude change, opinion change, behavioral change, and social change, are applied in this research. Employee loyalty, based on Siswanto’s definition (in Soegandhi et al., 2013), includes obedience to regulations, responsibility to the institution, cooperation, a sense of belonging, interpersonal relationships, and work passion. The study adopts a descriptive explanatory survey method. The population includes 30 employees engaged in railway crossing safety at the Garut Regency Transportation Service, using a saturated sampling technique for data collection. Data were gathered through questionnaires, observations, and interviews. Results indicate that work professionalism and communication have a significant effect on employee loyalty, accounting for 58.3% of the variance, while the remaining 41.7% is influenced by other factors outside the scope of this study. The study suggests that improving the professionalism of railway safety employees requires a deeper understanding of their profession to foster emotional stability and stronger interpersonal relationships. Enhanced communication support is also necessary to boost loyalty. Additionally, implementing a morning briefing routine could improve the efficiency and loyalty of railway safety employees at the Garut Regency Transportation Service, ultimately enhancing commitment to the organization.